(untitled) (Bangladesh Medical Journal, 2009)
With an objective to evaluate the impact of existing extracurricular activities at undergraduate medical and dental education in Bangladesh this descriptive study was designed and collected information conveniently from 515 students and 155 teachers from randomly selected medical and dental colleges of the country. The respondents (100%) supported more than one extracurricular activity for the medical and dental students. More than 65% were in favor of games, sports and cultural functions. Some students clubs are also popular among the respondents but only 10.8% respondents supported student politics. The respondents who were against student politics viewed that it hamper educational activities and disciplines in their institutes. About half the respondents (48.8%) were unsatisfied with the present academic activities in their medical colleges. Respondents advised to develop infrastructures, accommodation facilities, teaching aids, libraries, administrative supervisory in the institutes. They also demand more trained teachers, good students-teachers relationship to raise standard of the medical and dental colleges to a satisfactory level. Key words: Extracurricular activities, Evaluation, Impact. DOI: 10.3329/bmj.v37i1.3600 Bangladesh Medical Journal 37(1) 2008 6-9